Design and Build an Android-Based Student Attendance System Using LBS and Qrcode at IAIN Salatiga - Ayub Dwi Saputra, Maulana (Gayaku Publisher, 2022)
IAIN Salatiga as an educational institution continues to strive to make improvements where there are still processes that are carried out manually which can be improved with a touch of existing technology. One of the activities that can be improved from this learning process is the student attendance and attendance process, which previously was still carried out manually using How to provide an attendance list signed by the student, then the data is entered into the IAIN Salatiga academic information system application by manual input into the system. This process has several problems, firstly, attendance data is invalid, the second problem is that lecturers often forget to verify the attendance list that has been signed by students, attendance data stored in the database does not display the actual data in real time and sometimes there are courses that are not recorded in the database. teaching journal. The technological media chosen in this research are Android-based mobile devices, LBS and QR Code. The system developed is integrated with IAIN Salatiga's SI-Mona and SIAKAD applications so that lecturer teaching journal data, lecture evidence and student attendance lists become one undivided data unit